4x + 7 = 6x -7 14=2x so x = 7 (plus a negative # is simply - that number)
negative one and a half
y = -6x + 3 Multiply the slope by the negative reciprocal y = 1/6x + 3
6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.
6x+x = 7x
The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)
It is: 3x2+6x-11 = 0
6x plus 3y minus 2x plus 5y equals 4x plus 8y.
5x + x - 6x + 2x = 2x
6x plus 3 equals to 8x plus 14 would lead to x = - 5.5.
The coefficient of x2 is -3 which is negative. Therefore the curve is downward opening.
7x + 2 = 6x + 2 if and only x = 0.
6x + 34 = 4x +284 6x - 4x = 284 - 34 2x = 250 x = 125
16x+9 without the rest of the equation, what this equals, I can't solve
6x+4=52 6x=48 x=8